Cyclic modules and the structure of rings - Jain, S. K. (Surender Kumar), 1938-; Srivastava, Ashish K.; Tuganbaev, Askar A. (Oxford : Oxford University Press, 2013)
This monograph brings together important material in the field of noncommutative rings and modules. It provides an up-to-date account of the topic of cyclic modules and the structure of rings which will be of particular interest to those working in abstract algebra and to graduate students who are exploring potential research topics.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Noncommutative rings